2007
DOI: 10.2337/dc07-0002
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Pharmacokinetics and Dynamics of the Long-Acting Insulin Analogs Glargine and Detemir at Steady State in Type 1 Diabetes

Abstract: OBJECTIVE -To compare pharmacokinetics and pharmacodynamics of insulin analogs glargine and detemir, 24 subjects with type 1 diabetes (aged 38 Ϯ 10 years, BMI 22.4 Ϯ 1.6 kg/m 2 , and A1C 7.2 Ϯ 0.7%) were studied after a 2-week treatment with either glargine or detemir once daily (randomized, double-blind, crossover study).RESEARCH DESIGN AND METHODS -Plasma glucose was clamped at 100 mg/dl for 24 h after subcutaneous injection of 0.35 unit/kg. The primary end point was end of action (time at which plasma gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(180 citation statements)
references
References 28 publications
9
168
0
3
Order By: Relevance
“…In brief, two venous lines were inserted, an antecubital vein on one arm (for infusions) and a dorsal vein (cannulated retrogradely with a 20-gauge butterfly needle) on the contralateral hand (kept at 658C in a hot box) for intermittent sampling of arterialized venous blood. An intravenous feedback insulin infusion was initiated to achieve and maintain PG at 100 6 5 mg/dL until time 0 (i.e., 1000 or 2200 h), as previously described (21). At 2120 min, a primed sterile, pyrogen-free constant infusion (0.222 mmol/kg/min) of [6,6-2 H 2 ]-glucose (Cambridge Isotope Laboratories, Cambridge, MA) was started and maintained throughout the experiment to determine glucose kinetics.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, two venous lines were inserted, an antecubital vein on one arm (for infusions) and a dorsal vein (cannulated retrogradely with a 20-gauge butterfly needle) on the contralateral hand (kept at 658C in a hot box) for intermittent sampling of arterialized venous blood. An intravenous feedback insulin infusion was initiated to achieve and maintain PG at 100 6 5 mg/dL until time 0 (i.e., 1000 or 2200 h), as previously described (21). At 2120 min, a primed sterile, pyrogen-free constant infusion (0.222 mmol/kg/min) of [6,6-2 H 2 ]-glucose (Cambridge Isotope Laboratories, Cambridge, MA) was started and maintained throughout the experiment to determine glucose kinetics.…”
Section: Methodsmentioning
confidence: 99%
“…Also, in one head-to-head study in type 2 diabetic patients the two long-acting insulin analogues were found to be comparable [10], whereas another comparison in individuals with type 1 diabetes showed lower total activity and a shorter duration of action for insulin detemir [12]. Some have attributed these conflicting findings to differences in study design, such as the study insulin dose [12], or to inherent differences in the PD profiles in type 1 vs type 2 diabetic patients [10]. Others have simply labelled inconsistent results as 'outlier findings' [6].…”
Section: Conflicting Clamp Datamentioning
confidence: 94%
“…However, during manual clamps, (un)conscious investigator-related bias cannot be ruled out, despite attempted blinding of the study insulin. This may explain why manual clamp studies have reported different time-action profiles for the same longacting insulin analogue [12,15].…”
Section: Clamp Methodology: Biostator Vs Manual Clampmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from glucose clamp studies performed in healthy volunteers, 9,30 patients diagnosed with Type 1 diabetes mellitus 7,8,21 and Type 2 diabetes mellitus 22,23 have been published. However, for each population a number of potentially confounding factors must be considered when interpreting the results.…”
Section: Study Populationmentioning
confidence: 99%